Inhibition of co-colonizing cystic fibrosis-associated pathogens by Pseudomonas aeruginosa and Burkholderia multivorans - Costello, A.; Reen, F.; O'Gara, Fergal; Callaghan, M.; McLean, S. (Society for General Microbiology, 2014)
Cystic fibrosis (CF) is a recessive genetic disease characterized by chronic respiratory infections and inflammation causing permanent lung damage. Recurrent infections are caused by Gram-negative antibiotic-resistant bacterial pathogens such as Pseudomonas aeruginosa, Burkholderia cepacia complex (Bcc) and the emerging pathogen genus Pandoraea. In this study, the interactions between co-colonizing CF pathogens were investigated. Both Pandoraea and Bcc elicited potent pro-inflammatory responses that were significantly greater than Ps. aeruginosa. The original aim was to examine whether combinations of pro-inflammatory pathogens would further exacerbate inflammation. In contrast, when these pathogens were colonized in the presence of Ps. aeruginosa the pro-inflammatory response was significantly decreased. Real-time PCR quantification of bacterial DNA from mixed cultures indicated that Ps. aeruginosa significantly inhibited the growth of Burkholderia multivorans, Burkholderia cenocepacia, Pandoraea pulmonicola and Pandoraea apista, which may be a factor in its dominance as a colonizer of CF patients. Ps. aeruginosa cell-free supernatant also suppressed growth of these pathogens, indicating that inhibition was innate rather than a response to the presence of a competitor. Screening of a Ps. aeruginosa mutant library highlighted a role for quorum sensing and pyoverdine biosynthesis genes in the inhibition of B. cenocepacia. Pyoverdine was confirmed to contribute to the inhibition of B. cenocepacia strain J2315. B. multivorans was the only species that could significantly inhibit Ps. aeruginosa growth. B. multivorans also inhibited B. cenocepacia and Pa. apista. In conclusion, both Ps. aeruginosa and B. multivorans are capable of suppressing growth and virulence of co-colonizing CF pathogens.